1990
DOI: 10.1177/38.9.2117624
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural localization of blood-retinal barrier breakdown in diabetic and galactosemic rats.

Abstract: Breakdown of the blood-retinal barrier (BRB) is an early event in diabetic and galactosemic rats, but the location and nature of the specific defect(s) are controversial. Using an electron microscopic immunocytochemical technique, the retinas of normal, diabetic, and galactosemic rats were immunostained for endogenous albumin. Normal rats showed little evidence of BRB breakdown at either the inner barrier (retinal vasculature) or the outer barrier (retinal pigment epithelium) (RPE). In diabetic and galactosemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0
5

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 33 publications
5
40
0
5
Order By: Relevance
“…In respect of this observation it is inter esting to note that in a previous study leakage of tracers was observed in the peripapillary retina in some but not all of a series of normal rabbits and monkeys studied [15]. Further more, in a study of retinal permeability in rats using albumin as an endogenous tracer in creased permeability was found in the ani mals over 2 years of age, suggesting that aging may also lead to local barrier loss in the retinal microvasculature [22],…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In respect of this observation it is inter esting to note that in a previous study leakage of tracers was observed in the peripapillary retina in some but not all of a series of normal rabbits and monkeys studied [15]. Further more, in a study of retinal permeability in rats using albumin as an endogenous tracer in creased permeability was found in the ani mals over 2 years of age, suggesting that aging may also lead to local barrier loss in the retinal microvasculature [22],…”
Section: Resultsmentioning
confidence: 99%
“…In the study of eye diseases where these barrier functions arc lost or altered, such as uveitis and retinal vascular disease [22,23,29], this marker may be very useful.…”
Section: Resultsmentioning
confidence: 99%
“…Streptozotocin-treated diabetic rats have been widely used to investigate the mecha nisms of hyperpermeability of diabetic retinal vessels by detecting extravasation of intrave nously injected tracers [5,6] or by immunohistochemically detecting extravasation of plasma proteins [4,7], The aim of the present study was to look for VEGF, a potent perme ability factor, in retinas of streptozotocintreated diabetic rats using immunohisto chemistry. To identify the cells which produce VEGF, we also performed immunohisto chemistry for a-smooth muscle actin which is a marker for smooth muscle cells of arteries and veins as well as pericytes of capillaries [ 8],…”
Section: Discussionmentioning
confidence: 99%
“…Using a variety of non-MRI but physiologically relevant methods and tracers in diabetic or galactose-fed rats, investigators have reported little or no change in BRB permeability in early diabetes (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). In contrast, in a study using a nonquantitative histological detection method with an endogenous tracer (extravasation of albumin), only a subset of diabetic rats is reported to develop some leakage (45)(46)(47). In further contrast, there are many reports (47-51) of studies using non-physiologically relevant tracers and methods, such as fluorescein, albumin, or Evans blue dye, in which BRB damage occurs as early as 2 weeks after diabetes induction in rats.…”
Section: Brb Psmentioning
confidence: 99%